Suami perokok dan kejadian berat badan lahir rendah - Rinela Padmawati; Neli Nurlina; Dwi Amelia Nurillah (Poltekkes Kemenkes Yogyakarta, 2013)
LBW is newborns with a birth weight less than 2500 grams. one cause of low birth weight in developing counties according to the World Health Organization (WHO) in 2oo4 was the habit of smoking. Pregnant women as passive smokers have risks of having low birth weight babies because of the toxins in cigarettes that can impede blood flow. Thus, this interferes with the growth and development of babies. The objective of this study was to determine the relationship between smoking husband and the incident of LBW in the maternity ward of Waled Local Hospital in May 2013. The method uses was an analytical survey with a retrospective cohort design. The sampling technique was an accidental sampling. The population was all husband who’s a wife giving birth in Waled Local Hospital in May 2013 amounting to 157 persons. the samples in the study were 136 people. The study was conducted in May 2013. Data collection used spreadsheet instrument through direct questioning with the patients on the patient husband with an observation by measuring the baby weight using body weight scale. The data analysis used univariate with frequency distribution and bivariate with chi-square statistical test. The result showed that there were 38 babies with low birth weight (27.9%) and almost half of husband smoked near their wives by 61 persons (44.9%). The result bivariate analysis revealed that there was a significant relationship between smoking husband and the incidence of LBW. It is then recommended that health workers should improve and counseling on the dangers of secondhand smoke for mother and fetus in order to provide information to the public.